2002
DOI: 10.2337/diacare.25.10.1729
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Resistance Training Improves Glycemic Control in Older Patients With Type 2 Diabetes

Abstract: OBJECTIVE—To examine the effect of high-intensity progressive resistance training combined with moderate weight loss on glycemic control and body composition in older patients with type 2 diabetes. RESEARCH DESIGN AND METHODS—Sedentary, overweight men and women with type 2 diabetes, aged 60–80 years (n = 36), were randomized to high-intensity progressive resistance training plus moderate weight loss (RT & WL group) or moderate weight loss plus a control program (WL group). Clinical and labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
437
6
54

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 603 publications
(533 citation statements)
references
References 40 publications
36
437
6
54
Order By: Relevance
“…In line with several previous investigations (Dunstan et al 2002;Ibáñez et al 2008;28 Kwon et al 2010;Larose et al 2010), our findings showed an improvement of 29 13 muscle strength of T2D patients after training. However, in the present study we 1 demonstrate that the training was only effective in isometric contractions and 2 dynamic contractions of lower velocity.…”
Section: Patients 24supporting
confidence: 93%
“…In line with several previous investigations (Dunstan et al 2002;Ibáñez et al 2008;28 Kwon et al 2010;Larose et al 2010), our findings showed an improvement of 29 13 muscle strength of T2D patients after training. However, in the present study we 1 demonstrate that the training was only effective in isometric contractions and 2 dynamic contractions of lower velocity.…”
Section: Patients 24supporting
confidence: 93%
“…These authors used a progressive resistance training protocol that began at 60 % of 1 RM and progressed to 80 % of 1 RM (three sets of eight repetitions). A similar resistance training protocol was used in the study by Dustan et al (2002), who also investigated men and women with type 2 diabetes (aged 67 ± 5 years).…”
Section: The Effects Of Resistance Trainingmentioning
confidence: 99%
“…Meta-analyses and other studies have demonstrated that aerobic and resistance exercise each improves glycaemic control in people with this condition [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 98%